CHARACTERISTICS OF BOILING BUBBLE DEPARTURE DIAMETER AND FREQUENCY FROM POROUS FOAM STRUCTURES - Indro Pranoto; Umar Fadhil Ramadhan; Muhammad Habtry; Leong Kai Choong (Integrated Lab Journal, 2018)
An experimental study on the boiling phenomena and bubble dynamics from the porous graphite foams of different thermophysical properties with FC-72 dielectric coolant under saturated pool boiling condition is presented in this paper.  The pool boiling process from different graphite foams viz. “Pocofoam” of 61%, “Pocofoam” of 75%, “Kfoam” of 78% and “Kfoam” of 72% porosities were captured by using a high speed camera at 2005 frames per second and analyzed by using “Image Pro” image processing software. The bubble departure diameter and frequency from the porous foams are presented and discussed in this study. The results show that “Pocofoam” of 61% porosity has produced the smallest bubble departure diameter and highest bubble departure frequency as compared to other porous foams. It was found that the average bubble departure diameter and bubble frequency of “Pocofoam” of 61% porosity is 480.8 µm and 173 Hz, respectively.  The experimental results have also shown that the thermal properties of the porous graphite foam affected the bubble departure diameter and frequency.